The effects of formal and informal learning environments and strategies on the acquisition skills: Post-secondary learners' perceptions - Awang Faisal Awang Borhanuddin (2017)
There are multiple factors that can influence second language acquisition. One of the factors is whether English users acquire a second language in a formal or informal environment. This study aimed to determine whether learning English in a formal compared to an informal environment leads to different effects on their English skills. The study also aimed to determine whether learning strategies employed by English users differ in each learning environment. Identifying the appropriate language learning strategy in each language learning environment will allow learners to achieve optimal acquisition of language for their needs. This study is to give an account on what ways the language learning environment can affect the English users based on their perceptions and their strategies in acquiring English skills in their learning environment. Adopting both qualitative and quantitative research methods, the data collection was conducted through in-depth reflexive photography interview and questionnaire. The findings suggest that the informal learning environment is better in acquiring communication skills. Social interaction is the most frequently used strategy in the informal learning environment. This research can serve as a reference for learners, teachers and language educators to enhance English communication skills and utilize effective strategies in pursuing English language mastery.